An Analysis of Word Formation Processes on Cosmetic Product Descriptions in U.S Celebrities’ Beauty Brands - Citra Ayu Larasati; Pariyanto (JET ADI BUANA, 2022)
This research explored the types of word formation processes in the descriptions of cosmetic products. This descriptive qualitative study employed the classification of word formation processes proposed by Yule’s (2010)—derivation, compounding, conversion, borrowing, blending, acronym, backformation, coinage, clipping, and multiple processes to analyze the data. The data were taken from the descriptions of cosmetic products in the beauty brands by U.S celebrities—Fenty Beauty, Rare Beauty, Kylie Cosmetics, and Florence by Mills which were released and in production in April, 2022. This study discovered 125 word-formation processes including derivation (42), conversion (29), multiple processes (17), compounding (16), clipping (8), borrowing (7), acronym (3), coinage (2), and blending (1). This study implies that derivation is the most frequently used in the product descriptions, suggesting that the use of derivation creates adjectives that modifies the products.